Optimization of L-tryptophan and thiotriazoline compound analysis by high-performance liquid chromatography - L. I. Kucherenko; S. A. Borsuk; I. A. Mazur; L. G. Cherkovska; D. Yu. Skoryna (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
Introduction. An actual task of modern medicine is the development of treatment methods of the central nervous system diseases. The solution of this problem was the creation of new, more effective neuropsychotropic drug that shows pronounced antidepressant, nootropic, neuroprotective and antioxidant effects based on the fixed combination of L-tryptophan with thiotriazoline. One of the steps in creating a new drug is the standardization of active ingredients.